ANALISIS PENGARUH KEPEMILIKAN INSTITUTIONAL, BOOK TAX DIFFERENCE DAN KOMITE AUDIT TERHADAP PERSISTENSI LABA : STUDI PADA PERUSAHAAN TECHNOLOGY, FOOD & BEVERAGE YANG TERCATAT DI BEI - Hasanah, Nur; Wibowo, Agus Satrya; Setiawan, Ricky Yunisar (LPPM Universitas Bina Bangsa, 2025)
This study is focused on evaluating the determinants of profit persistence in the context of Technology, Food and Beverage companies listed on the Indonesia Stock Exchange throughout the 2021-2023 period. Through quantitative methodologies and purposive sampling strategies, this comprehensive study explores the influence of institutional ownership, tax bookkeeping differences, and the existence of audit committees on the quality and consistency of corporate profits. The study used a sample of 66 companies, with variable constructs that included institutional ownership, book tax difference, and audit committee as independent variables, while profit persistence was set as a dependent variable. Data analysis was carried out using multiple linear regression, equipped with a series of statistical prerequisite tests to ensure the validity and reliability of the research results. The academic contribution of this study lies in the development of an in-depth theoretical framework related to the fundamental factors that affect profit persistence, with a particular focus on the Technology, Food and Beverage sector. In practical terms, the findings of the study are expected to provide an empirical foundation for stakeholders, including investors, regulators, and company management, in strategic decision-making and efforts to improve the quality of financial reporting